HUBUNGAN KECANDUAN GAME ONLINE MOBILE LEGEND BANG-BANG (MLBB) TERHADAP KUALITAS TIDUR REMAJA DI KELURAHAN PASIR PANJANG KUPANG - Silla, Angriani; Lao, Hendrik (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2024)
Online games are games played through an internet connection, the phenomenon that occurs today is game addiction felt by teenagers in kupang who have unstable sleep quality due to addiction to online games, especially mobile legend bang-bang. This study aims to determine the relationship between addiction to mobile legend online games and the quality of sleep of adolescents in the long sand village of Kupang. The methods used in this study were quantitative and tests involving 30 subjects randomly selected from the adolescent population in Pasir Panjang. The research results of this article are the relationship between MLBB online game addiction and adolescent sleep quality in Pasir Panjang Kupang village. With a correlation test result of 0.794 or 79.4% which is included in the high category.